2012
DOI: 10.1039/c2dt12117d
|View full text |Cite
|
Sign up to set email alerts
|

Forming trifluoromethylmetallates: competition between decarboxylation and C–F bond activation of group 11 trifluoroacetate complexes, [CF3CO2ML]−

Abstract: A combination of gas-phase 3D quadrupole ion trap mass spectrometry experiments and density functional theory (DFT) calculations have been used to examine the mechanism of thermal decomposition of fluorinated coinage metal carboxylates. The precursor anions, [CF(3)CO(2)MO(2)CCF(3)](-) (M = Cu, Ag and Au), were introduced into the gas-phase via electrospray ionization. Multistage mass spectrometry (MS(n)) experiments were conducted utilizing collision-induced dissociation, yielding a series of trifluoromethylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 94 publications
2
49
1
1
Order By: Relevance
“…Unfortunately, CID experiments revealed that instead of decarboxylation occurring, all of these complexes fragmented to produce [(phen)Ni(X)] + as the sole CID product (data not shown). These reactions are likely to proceed via similar C―X bond activation mechanisms found for losses of CF 2 CO 2 from the coinage metal trifluoroacetates, [(CF 3 CO 2 ) 2 M] − (where M = Cu, Ag, and Au) …”
Section: Resultsmentioning
confidence: 89%
“…Unfortunately, CID experiments revealed that instead of decarboxylation occurring, all of these complexes fragmented to produce [(phen)Ni(X)] + as the sole CID product (data not shown). These reactions are likely to proceed via similar C―X bond activation mechanisms found for losses of CF 2 CO 2 from the coinage metal trifluoroacetates, [(CF 3 CO 2 ) 2 M] − (where M = Cu, Ag, and Au) …”
Section: Resultsmentioning
confidence: 89%
“…The difference between the previous studies and this work is that the α-lactone formed upon fragmentation chargeremote fragmentation of PheSO 3 À is ionic, and therefore detectable by mass spectrometry. Previous studies of halogenated carboxylates [48][49][50][51] have inferred α-lactone structures based on the observation of halide products.…”
Section: Resultsmentioning
confidence: 99%
“…[11a] Virtually identical average AuÀF interatomic distances were found in the neutral metallacyclic difluorides (N^C)AuF 2 (198.2(4) pm av.). By far the most favored process involves CF 2 extrusion [14] and formation of the trifluoride complex [CF 3 AuF 3 ] À with no change in the metal oxidation state (Scheme 2a). It undergoes various collision-induced dissociation processes (Figures S8-S12), which are summarized in Scheme 2.…”
mentioning
confidence: 99%